European Labor Markets and the COVID-19 Pandemic : Fallout and the Path Ahead - Ando, Sakai; Balakrishnan, Ravi.; Gruss, Bertrand; Hallaert, Jean-Jacques. (Washington, D.C. : International Monetary Fund, 2022)
In 2020, the COVID-19 pandemic caused by far the largest shock to European economies since World War II. Yet, astonishingly, the EU unemployment rate had already declined to its pre-crisis level by 2021Q3, and in some countries the labor force participation rate is at a record high. This paper documents that the widespread use of job retention schemes has played an essential role in mitigating the pandemic's impact on labor markets and thereby facilitating the restart of European economies after the initial lockdowns.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Human Capital; Employment; Intergenerational Income Distribution; Unemployment; Wages